Analisis Faktor Tidak Meratanya Pendidikan Di Sdn0704 Sungai Korang - Ria Renata Ginting; Egi Verbina Ginting; Roudhotul Jannah Hasibuan; Laurensia Masri Perangin-angin (Jurnal Pendidikan Indonesia, 2022)
The problem in the world of education today is regarding the non-achievement of educational development targets, which is seen from the unequal access to education, the low proportion of teachers who have high academic qualifications, limited facilities and infrastructure, and so on. The purpose of this study is to analyze the factors that cause inequality in education in elementary schools, specifically at SDN0704 Sungai Korang. This research method is a qualitative descriptive research method using a qualitative approach, namely describing the analysis of the factors of inequality in education at SD Negeri 0704 Sungai Korang. The results of the study explain that the implementation of education at SDN0704 Sungai Korang has not been running effectively, which is seen from the change in the curriculum that often inconsistent, making it difficult for students to understand the essence of learning, lack of facilities is a major problem for the school, also seen from the low quality of teachers when compared to teachers in advanced urban schools. Thus, it can be concluded that education in Indonesia needs to get more attention and be addressed by the government, one of which is increasing the budget and improving the quality of the teaching staff (teachers). Quality teachers are the key in the formation of good students and education is the key to the progress of the country's development.